Annual review of comparative and international education 2018 - Wiseman, Alexander W. (International perspectives on education and society ;, 2019)
Since 2013, the Annual Review of Comparative and International Education has covered the significant developments in the field of comparative and international education. This year's edition begins with a collection of reflective essays about comparative education trends and directions written by both professional and scholarly leaders in the field. Topics covered in the 2018 volume include major theoretical and methodological developments, reports on research-to-practice, area studies and regional developments, and the diversification of comparative and international education. A special introductory chapter addresses the "osmosis" of comparative and international education research across field and disciplinary boundaries.This book sheds light on the most recent advances and patterns within the field of comparative education and will prove an essential text for researchers in the field of global education.